Multimedia Pembelajaran Bahasa Arab Berbasis Mobile - Andy Fahmi Halim (STAI Ali bin Abi Thalib Surabaya, 2018)
In the entire parts of human life, keeping on being developed and advanced all the time makes the technology has become a part of life that is difficult to escape from. One of the most useful uses of it is in the educational field. By using its advanced technology, the educational system has made it easy for both educators and students. Nowadays, every mobile devices is possibly applied to learn, particularly to learn Arabic. Through this device, Arabic study will develop so rapidly that students with higher quality than the previous one are effectively produced. In addition, it can increase their interaction, as well as their motivation and enthusiasm to learn. Well-learning method are those being related to the recent one and in accordance with the students' developing skill. So, to be more effective is by applying the up-to-date learning method inasmuch as students can take advantage of the existing information and technology, and be more actively involved in learning, such as expressing opinions, and analyzing the problem.